Application of Peleg and Page's experimental models during osmotic dehydration and convective drying of tomato halves (Solanum lycopersicum L.) - Soto Jiménez, Luis Ricardo (2024)
The phenomenon of mass transfer during osmotic dehydration and convective drying of tomato halves (Solanum lycopersicum L.) was carried out 1) using sucrose and salt as solutes; and 2) by fitting the Peleg and Page equations to the experimental data. The fruit was cut into halves and its seeds and placenta were removed. It was osmotically dehydrated with solutions: 10.8% 18% and 30% 50%, (w/v), of salt and sucrose respectively at a temperature of 25 °C. Subsequently, the resulting samples were subjected to a convective drying process by forced air in a tunnel at temperatures of: 50; 70 and 90ºC. Determining the weight loss of the samples, the solids gain, obtaining parameters from the experimental models of Peleg and Page with correlation levels of R2 ≥0.9894 for the proposed models.